EVALUATION OF THE IMPLEMENTATION OF THE “ISLAM MELAYU NUSANTARA” POLICY AS A DISTINGUISHING OF UIN RADEN FATAH - Afriantoni, Afriantoni,; Zaini, Herman Zaini (Universitas Islam Negeri Raden Fatah Palembang, 2021)
Higher education is an institution that nurtures the birth of quality intellectual resources. Universities contribute to improving the quality of Human Resources (HR), including the Raden Fatah State Islamic Institute (IAIN) as one of the Islamic Universities located in Palembang City. Factually, IAIN Raden Fatah developed and planned the institutional change of IAIN into Raden Fatah State Islamic University (UIN). The development effort has been carried out since 2003. This effort is interesting to be studied and investigated in more depth. As a public organization, the vision of the organization is very important and determines the wheels of the organization affecting the overall mission and management mechanism. IAIN's organizational vision affects the organizational structure, science and the role of institutions as pioneers of change and readiness to face global competitiveness. The purpose of this study is to describe the formulation of the vision, development of scientific orientation and competitiveness as the basis of the campus management's efforts in carrying out a process of change. Change management is carried out as a theoretical framework to find out the process carried out by IAIN to achieve the big goal of becoming UIN Raden Fatah. It is recognized that the changes made have taken at least 10 years, and in 2014 began to see results. The results of this study indicate that the vision that was initiated, formulated and implemented as a reference for the entire academic community of IAIN Raden Fatah, which was recorded 19 times, underwent changes and greatly influenced the institutional performance in achieving these great goals. In the scientific context, the scientific model formulated by Ismail about the